2021
DOI: 10.1371/journal.ppat.1009940
|View full text |Cite
|
Sign up to set email alerts
|

PCV2 targets cGAS to inhibit type I interferon induction to promote other DNA virus infection

Abstract: Viruses use diverse strategies to impair the antiviral immunity of host in order to promote infection and pathogenesis. Herein, we found that PCV2 infection promotes the infection of DNA viruses through inhibiting IFN-β induction in vivo and in vitro. In the early phase of infection, PCV2 promotes the phosphorylation of cGAS at S278 via activation of PI3K/Akt signaling, which directly silences the catalytic activity of cGAS. Subsequently, phosphorylation of cGAS at S278 can facilitate the K48-linked poly-ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…Studies have shown that some circoviruses affect the host interferon response [ 21 ]. The innate immune response is the first line of defense of a host.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some circoviruses affect the host interferon response [ 21 ]. The innate immune response is the first line of defense of a host.…”
Section: Introductionmentioning
confidence: 99%
“…During the infection, the viral Cap can inhibit ubiquitin-mediated proteasomal degradation of cellular C1QBP, thus further enhancing the phagocytic activity of PAM through the PI3K pathway [ 127 ]. Furthermore, the interaction of viral Cap and host C1QBP also promotes phosphorylation of cyclic dinucleotide GMP-AMP (cGAMP) synthase (cGAS) via PI3K/Akt and PKCδ signal pathways [ 128 ]. Then, the release of cGAMP is enhanced, which binds to the Stimulator of Interferon Genes (STING) and induces dimerization and translocation of STING into the nucleus, resulting in an enhancement of IFN-β production [ 128 , 129 ].…”
Section: Crosstalk Between Pcv and Hostmentioning
confidence: 99%
“…Furthermore, the interaction of viral Cap and host C1QBP also promotes phosphorylation of cyclic dinucleotide GMP-AMP (cGAMP) synthase (cGAS) via PI3K/Akt and PKCδ signal pathways [ 128 ]. Then, the release of cGAMP is enhanced, which binds to the Stimulator of Interferon Genes (STING) and induces dimerization and translocation of STING into the nucleus, resulting in an enhancement of IFN-β production [ 128 , 129 ]. Additionally, PCV2 infection also activated retinoic acid-inducible gene I (RIG-1, DDX58), melanoma differentiation-associated protein 5 (MDA-5), and mitochondria antiviral-signaling protein (MAVS), which then led to the enhancement of downstream molecules, such as IFN regulatory factor 3 (IRF3) and IRF7, and thereby the expression of IFN-β gene was increased [ 130 , 131 ].…”
Section: Crosstalk Between Pcv and Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies revealed several viruses are capable to subvert selective autophagy to counteract IFN signaling cascade by promoting autophagic degradation of key components in IFN pathway. To attenuate the activation of IFN signaling, porcine circoviruses type 2 (PCV2) could induce phosphorylation of cGAS at S278 via activation of PI3K/Akt signaling which abolishes cGAS’s catalytic activity, and subsequently promote the K48-linked ubiquitination of cGAS, which is targeted by HDAC6 and delivered to autolysosome for degradation ( Wang Z. et al, 2021 ). In addition to degrade viral receptors, several viruses promote the autophagic degradation of adaptor proteins in IFN pathway to block signal amplification.…”
Section: Viral Strategies For Counteracting Selective Autophagymentioning
confidence: 99%